1998
DOI: 10.1002/(sici)1097-0010(199803)76:3<357::aid-jsfa955>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Response of nutrient digestibilities to feeding diets with low and high levels of soybean trypsin inhibitors in growing pigs

Abstract: : Studies were carried out to determine the e †ect of dietary soybean trypsin inhibitor (SBTI) content on nutrient and energy digestibilities in growing pigs. Six barrows, average initial body weight (BW) 47É8^4É0 kg, were Ðtted with a simple T-cannula at the distal ileum and fed two diets according to a crossover design. Two maize starch-based diets were formulated to contain 200 g crude protein (CP) kg~1 from either Nutrisoy (a food-grade defatted soy Ñour) or autoclaved Nutrisoy. The contents of SBTI in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…If the dietary TI reached 3.33 mg g −1 in the diet, then AID of amino acids and CP will be substantially reduced by 13.3–26.0% points. This reduction is less than Li's report (Li et al, 1998) in which SBM TI in the diet was 13.4 mg g −1 , much higher than this study, and it decreased CP digestibility by 39.7% points (from 77.1% to 37.4%), AID of Met and…”
Section: Resultscontrasting
confidence: 82%
“…If the dietary TI reached 3.33 mg g −1 in the diet, then AID of amino acids and CP will be substantially reduced by 13.3–26.0% points. This reduction is less than Li's report (Li et al, 1998) in which SBM TI in the diet was 13.4 mg g −1 , much higher than this study, and it decreased CP digestibility by 39.7% points (from 77.1% to 37.4%), AID of Met and…”
Section: Resultscontrasting
confidence: 82%
“…Similar results were achieved in our study. Many studies have found that protein digestibility was decreased by 20-40% in animals fed diets containing raw soybean or high levels of TI compared with those fed diets containing heated soybeans or SBM (Qin 1996;Caine et al 1998;Li et al 1998) compared with conventional soybeans when fed to growing pigs. Likewise, Herkelman et al (1992) showed that lowtrypsin-inhibitor soybean had significantly greater amino acid and nitrogen digestibility compared with conventional soybean when fed to growing pigs.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, what are the prospects that microbial proteins, relatively rich in amino acids essential to vertebrate hosts (Kinnear et al, 1979), are degraded in the hindgut to small peptides and free amino acids that can be absorbed? Certainly, whole-animal studies may show evidence of protein digestion in hindgut, but if protein is largely degraded by hindgut microbes and then absorbed largely as ammonia, as is often thought to be the case (Li, Sauer & Caine, 1998), this achieves relatively little benefit in regards to satisfying requirements for essential amino acids. Indeed, if the immediate source of the microbial N was the host's urea, uric acid, or high-protein urate ''spheres'' (Braun, 2003), then one might ask whether the net effect of this kind of microbial cycling of N is anything more than a futile cycle, at least from the perspective of the host's N economy.…”
Section: The Role Of the Avian Hindgut In Nutritionmentioning
confidence: 99%